Pharmacological correction of periodontitis using synthetic analogues of indolicidin - Igor V. Kutepov; Yuri D. Lyashev (Research Results in Pharmacology, 2019)
Introduction: The leading role of pathogenic microorganisms in the pathogenesis of periodontitis is beyond doubt. However, the use of antibiotics for periodontitis is associated with a number of problems. Indolicidins have a unique anti-microbial effect. The relevance of the search for new drugs for the treatment of acute periodontitis based on the natural indolicidin peptide becomes obvious.